Pengembangan Pariwisata Berkelanjutan Berbasis Masyarakat Di Desa Simamora Kecamatan Baktiraja, Kabupaten Humbang Hasundutan - Julianto, Julianto (Politeknik Pariwisata Medan, 2023)
Simamora Village, Baktiraja District, Humbang Hasundutan Regency is one of the areas in North Sumatra which has great tourism potential. Simamora Village has an attractive natural beauty with shady trees, cool air, and beautiful scenery. Simamora Village also has unique arts and cultural activities, such as traditional dances and gondang music. However, tourism development in Simamora Village is not yet optimal and not sustainable. Therefore, this study aims to develop community-based sustainable tourism in Simamora Village, Baktiraja District, Humbang Hasundutan Regency. The analysis technique used in this study is research that produces descriptive data in the form of written or spoken words from people and observed behavior. Meanwhile, descriptive research is a form of research aimed at describing or describing existing phenomena, both natural phenomena and human engineering. There are also conclusions from this study. The tourism potential of Simamora Village is very large, especially natural and cultural tourism. However, this potential has not been properly maximized due to a lack of attention and support from the government and the local community. The development of community-based sustainable tourism in Simamora Village can be carried out by strengthening the community's role in the management and development of tourism, so as to improve the economic welfare of the local community. In developing community-based sustainable tourism, it is necessary to carry out a participatory approach between the government, the community and other tourism actors. Strengthening the local economy can be done through developing unique and sustainable tourism products, developing homestays and local restaurants, and empowering local communities as tourism business actors. Support and coordination between stakeholders is needed in the development of community-based sustainable tourism in Simamora Village, especially support from the local government in terms of infrastructure and regulations.Keywords: Tourism development, Sustainable Tourism, Community Based Tourism